The Relationship between Glucosinolates and the Sensory Characteristics of Steamed-Pureed Turnip (Brassica Rapa subsp. Rapa L.) - Nurfarhana Diana Mohd Nor; Stella Lignou; Luke Bell; Carmel Houston-Price; Kate Harvey; Lisa Methven (Foods, 2020)
Glucosinolates (GSLs) are phytochemical compounds that can be found in Brassica vegetables. Seven separate batches of steamed-pureed turnip were assessed for GSL content using liquid chromatography mass spectrometry (LC-MS) and for sensory attributes by sensory profiling (carried out by a trained sensory panel). Twelve individual GSLs, which included 7 aliphatic, 4 indole and 1 arylaliphatic GSL, were identified across all batches. There were significant differences in individual GSL content between batches, with gluconasturtiin as the most abundant GSL. The total GSL content ranged from 16.07 to 44.74 μmol g−1 dry weight (DW). Sensory profiling concluded there were positive correlations between GSLs and bitter taste and negative correlations between GSLs (except glucobrassicanapin) and sweet taste. The batches, which had been purchased across different seasons, all led to cooked turnip that contained substantial levels of GSLs which were subsequently all rated as bitter.